The impact of zygote vitrification timing on pregnancy rate in frozen-thawed IVF/ICSI cycles - Makieva, Sofia; Stähli, Celine; Xie, Min; Gil, Ana Velasco; Sachs, Maike Katja; Leeners, Brigitte (Frontiers in Cell and Developmental Biology, 2023)
Cryopreservation of bipronuclear (2PN) stage zygotes is an integral part of IVF laboratory practice in countries with strict embryo culture legislation. Vitrification of zygotes is compatible with several strategies in infertility treatments holding a freeze-all indication and allows for effective workload management in settings with limited resources. Although it yields high survival rates and clinical outcomes, the ideal timing to commence vitrification of zygotes is elusive while it is empirically practiced in the window between 17 and 21 hours post-insemination (hpi). We aimed to deduce the association between pregnancy rate and the time interval from insemination (IVF and ICSI) to vitrification to contribute to the standardization of zygote cryopreservation. A retrospective analysis of data on vitrification timings and pregnancy outcomes collected between 2011 and 2019 was performed. All included women received an embryo transfer after warming of vitrified zygotes at the 2PN stage. A total of 468 embryo transfers were included of which 182 (38.9%) resulted in pregnancy and 286 (61.1%) not. Vitrification was on average performed 18.74±0.63 hpi in the pregnant group and 18.62±0.64 hpi in the non-pregnant group (OR 1.36, 95% CI 1.01; 1.83, p=0.045). A multivariate analysis controlling for uterine pathologies, maternal age, AMH, the number of MII oocytes, previous history of pregnancy success, endometriosis, AFC, nicotine intake and male factor infertility showed no predictive value of vitrification timing on pregnancy rate. Three time intervals between insemination and vitrification were defined: 17:00 to 18:00 hpi (Group A), 18:01 to 19:00 hpi (Group B) and 19:01 to 21:00 hpi (Group C). Pregnancy occurred in 40/130 women (30.80%) in Group A, in 115/281 women (40.90%) in Group B and in 27/57 women (47.40%) in Group C. Univariate but not multivariate analysis showed a significantly higher pregnancy rate after the latest time interval between insemination and 2PN vitrification when compared to the earliest (Group C vs A, OR 2.03, 95% CI 1.07; 3.84, p=0.031). These findings encourage further investigation on the impact of vitrification timing on clinical outcomes and hold the potential to standardize cryopreservation of zygotes from IVF/ICSI cycles to eventually improve the quality of long-term ART outcomes.